FUNCTIONAL VALUE ANALYSIS OF TOURISTS' REVISIT INTERESTS TO SUPER PRIORITY LAKE TOBA WITH WORD OF MOUTH AS MEDIATION - Megasari Gusandra Saragih; Mesra B (Green Publisher, 2022)
The study was studied to determine the effect of functional value on the revisit intention of tourists to the super priority tourist attraction of Lake Toba with word of mouth as mediation. The problem is finding a decrease in the number of tourist visits to the super priority tourist attraction of Lake Toba during the covid-19 pandemic. The samples are 140 tourists who have visited Lake Toba, with a non-probability sampling technique with a purposive sampling approach. Path analysis becomes the model of this research using AMOS 24.0 analysis tool. The results of the study found that the functional value has a significant effect on tourist word of mouth in the super-priority tourism of Lake Toba. Functional value and word of mouth had a significant effect on tourist revisit intention in the super-priority tourism of Lake Toba. Word of mouth partial mediates the effect of functional Value on tourist's revisit intention to super-priority tourism of Lake Toba